A study on business development strategies and tactics in the shipping industry to improve customer satisfaction (shipping lines) - Sorfina Fadzlon (2017)
Technology adoption in the container shipping lines has been gaining popularity in the past years, in both the industry and academia. Past researches focuses on the future potential of technology but little focus is on how disruptive technology impacts the container shipping industry in the current climate. Disruptive technology discussed will be in terms of Internet of Things (IoT) and Big Data Analytics. The container industry is gradually showing signs of recovery, thus investments in technology may be more common now as organisation compete to be ahead of its competitors. The objective of this paper is to examine whether shipping lines are considering the use of disruptive technology, since the global economy is gravitating towards an age of digitalisation. It aims to investigate if the adoption of disruptive technology is crafted towards increasing customer satisfaction. Apart from container shipping lines, two other major players will be analysed - they are Logistics Service Providers (LSPs) and Port Sector. These sectors would be covered by the author’s teammates. Past literature works on technology in the supply chain were analysed. Primary research was conducted in the form of survey questionnaires and face to face interviews. The interviews were to gain deeper insights and clarify any doubts with regards to the survey responses. There are relevant excerpts in the Appendices that were used to substantiate the arguments of this research paper. The distinction between disruptive and advanced technology is blurred as it is ultimately defined by the organisation's current state of operations and the market's technological trends. The technology adopted depends on the level of collaboration between various parties in the container shipping industry. Higher levels of collaboration would raise an added challenge for organisations. Leadership of an organisation is essential for it to sustain its competitive edge and strengths. Given the dampened freight rates and downturn in the global economy, the organisation looks to its leaders to steer them through the obstacles. Apart from minimising costs, the use of technologies or e-channels would be considered basic in the age of digitalisation. Lastly, the industry will succeed by having an industry leader to lead the market in the technological and research and development (R&D) initiatives.